New Design of Interactive Academic Supervision using the Waterfall Method to Improve Teachers' Pedagogical Competence - Pramita, Septiana; Satyawati, Sophia Tri; Wahyudi (Universitas Pendidikan Ganesha, 2024)
One strategy for increasing a teacher's pedagogical competence is through academic supervision. However, its implementation has experienced many obstacles, so it has yet to improve teachers' pedagogical competence successfully. This research aims to develop a new design for interactive academic supervision using the waterfall method to improve teacher pedagogical competence. This type of research is Research and Development (R&D) using the ADDIE model with a Mixed Method (sequential exploratory) approach. Research subjects included school principals, deputy principals for curriculum, and teachers. Data collection techniques were done through interviews, documentation studies, observation, FDG, and questionnaires. The data collection instrument is a questionnaire. The data analysis techniques used in this research are qualitative descriptive analysis and quantitative descriptive analysis. The research results produce a waterfall-based academic supervision model and guide called SUPER WATER. Product validation results by supervision experts were 88%, and IT experts were 94% in the very high category. The test results by the principal were 91%, and five teachers were 91%. It was concluded that this product is suitable for use. This research implies that Waterfall is an alternative technology that can be used to overcome problems that arise at this time.